2019
DOI: 10.1016/j.corsci.2019.108109
|View full text |Cite
|
Sign up to set email alerts
|

A multi-technique study of “barrier layer” nano-porosity in Zr oxides during corrosion and hydrogen pickup using (S)TEM, TKD, APT and NanoSIMS

Abstract: • Fresnel imaging in the TEM has been used to identify different types of porosity in the protective oxide near the "barrier layer", around 0~200nm from the metal-oxide interface. • More disorganised oxide grains and nano-porosity network is found by TEM and TKD in rapidly oxidising samples. • NanoSIMS analysis suggests that the transition event enables the propagation or trapping of deuterium while the pre-transition sample is a good barrier to deuterium penetration. • APT data provides strong direct evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…TEM studies showed a variety of small crack shapes in different locations in these oxides [15,65,66], and the use of Fresnel imaging was introduced as a powerful technique for detecting nanoscale porosity [22]. More recently, the emphasis has shifted to the analysis of systematic differences in pore density and distribution as a function of stage of the oxidation process [38], alloy chemistry [19] and irradiation [67,68]. This work has shown that the porosity depends on all of these parameters, and can vary significantly with the location in the oxide, but the general conclusion that can be drawn from these observations is that porosity is formed preferentially at oxide grain boundaries in most samples, and that interconnected chains of pores may be an easy path for the penetration of hydrogenic species through the growing oxide layer.…”
Section: Discussion Of Mechanisms Of Deuterium Permeation Through The...mentioning
confidence: 99%
See 1 more Smart Citation
“…TEM studies showed a variety of small crack shapes in different locations in these oxides [15,65,66], and the use of Fresnel imaging was introduced as a powerful technique for detecting nanoscale porosity [22]. More recently, the emphasis has shifted to the analysis of systematic differences in pore density and distribution as a function of stage of the oxidation process [38], alloy chemistry [19] and irradiation [67,68]. This work has shown that the porosity depends on all of these parameters, and can vary significantly with the location in the oxide, but the general conclusion that can be drawn from these observations is that porosity is formed preferentially at oxide grain boundaries in most samples, and that interconnected chains of pores may be an easy path for the penetration of hydrogenic species through the growing oxide layer.…”
Section: Discussion Of Mechanisms Of Deuterium Permeation Through The...mentioning
confidence: 99%
“…Atom probe tomography (APT) allows the analysis of trace element distributions at nanoscale spatial resolution and with a higher sensitivity than can be achieved by Transmission Electron Microscopy (TEM) analysis [31,32], but it is limited by complicated sample preparation, and the relatively low mass resolution [33,34] can also make it challenging to resolve interferences between different hydrogen-containing molecular ions. SIMS has been used to characterise elemental distributions in a wide variety of samples [35][36][37][38], and combines excellent depth resolution with high sensitivity for light elements and so is a powerful technique for mapping the interaction of hydrogenic species with the oxide layers formed on zirconium alloys. We have already shown that high-resolution SIMS analysis of oxidised zirconium alloys using a CAMECA NanoSIMS 50 instrument enables the mapping of hydrogen distributions at a sub-micrometre scale with no elaborate sample preparation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extremely low solid solubility of Fe in ZrO 2 , when Zr matrix around Zr(Nb,Fe,Cr) 2 is oxidized, Fe will be discharged and aggregated at SPPs boundaries [26]. Meanwhile, others have also found the phenomenon of Fe segregation at oxide grain boundaries [27]. There are different opinions on how Li and O enter oxide films and how they affect the corrosion resistance of zirconium alloys.…”
Section: Distribution Of Elements In Oxide Filmsmentioning
confidence: 99%
“…Dreano et al found that the temperature threshold of tribo-sintering of a cobalt-based superalloy (HS25) versus alumina contact was about 150 °C, and a protective oxide layer was formed when the temperature was higher than 150 °C [29]. In addition, the main compositions of the oxide film were ZrO, tetragonal ZrO 2 and monoclinic ZrO 2 formed by the aqueous oxidation of Zr alloy substrate [30]. Kim et al presented that the reduction of compressive stress would cause the phase transformation of tetragonal ZrO 2 to monoclinic ZrO 2 [31].…”
Section: Introductionmentioning
confidence: 99%